Risk Management Analysis Based on Supply Chain Business Process for Public Private Partnership Public Housing - Erman Sumirat; Sulaeman Rahman Nidar; Aldrin Herwany; Sudarso Kaderi Wiryono (International Journal of Supply Chain Management, 2020)
Covid19 Pandemic has made many countries like Indonesia spent their budget heavily on health and economy recoveries, meaning that some allocated budget including for infrastructure has been cut. In contrast, number of backlogs which determine numbers of people that need shelters are still remain high especially for low income groups (LIG). To tackle the problem, government has an initiative to engage private sectors through public private partnership (PPP) in public housing. The process is quite complex and has taken so many stakeholders like government, private sectors, consultants, contractors, vendors, subcontractors and financial institutions like banks and insurance companies. The complexities in PPP business models which involving so many stakeholders can create potential risks. Therefore, besides calculating investment return in the feasibility study stage, it is also important to make a risk management analysis based on supply chain business process. The supply chain business process must start from mapping business process, i.e. planning stage, contract award stage, implementation and the phase of hand over the facilities once the concessional period would end, transfer the ownership back from private sectors to government. This study has an objective to conduct literature study about risk management analysis by using ISO 31000: 2018, the relative new concept in risk management that replaces the same standard but from year of 2009. The model then will be combined with supply chain business process so risk management can be mitigated in each business process. The model of the study use supply chain business process in establishing the context in risk analysis followed by risk identification, risk analysis, risk evaluation with the integrated process of communication and consultation, recording and reporting as well as reviewing and monitoring. Study has found that there are critical risks that must be mitigated namely design risk, land price risk, legal land status risk, political risk, contractual risk, market risk, business risk, material price risk, operational risk, legal risk in hand over and asset impairment risk. The model has proposed several new techniques to mitigate risk namely using value at risk (VaR) by monte carlo simulation to measure market risk, business risk and operational risk, developing digitalization for the process in communication communication, recording reporting as well reviewing monitoring. It is also recommended the using of supply chain financing to vendors and subcontractors as Banks have the accessed data from digitalization that consider government and private sectors’ guarantees.